1995
DOI: 10.1111/j.1432-1033.1995.042_1.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunoassay for the Quantification of Intracellular Multi‐Ubiquitin Chains

Abstract: A sandwich ELISA has been developed to measure intracellular levels of multi-ubiquitin chains. The mixture of multi-ubiquitin chains, prepared in vitro by incubation of ubiquitin (plus "'I-ubiquitin) and lysozyme with ubiquitin-ligating enzymes and ATP, was partially purified and established as a standard named the multi-ubiquitin-chain reference preparation 1 (MUCRPI). The concentration of MUCRPI was calculated from the recovered radioactivity of "'I-ubiquitin. All measurements by the ELISA were expressed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 32 publications
(42 reference statements)
0
38
0
Order By: Relevance
“…The development of monoclonal antibodies recognizing polyubiquitin but not monoubiquitin facilitated the targeted analysis of polyubiquitinated material [69]. One of these monoclonal antibodies (FK2) was selected because of its high specificity toward polyubiquitinated proteins [70] and was first introduced in proteomic studies of the ubiquitinome [71] ( Figure 4C). This study identified 670 proteins that were enriched under highly denaturing conditions, but lacked the detection of GG-peptides…”
Section: Ubiquitin-specific Antibodiesmentioning
confidence: 99%
“…The development of monoclonal antibodies recognizing polyubiquitin but not monoubiquitin facilitated the targeted analysis of polyubiquitinated material [69]. One of these monoclonal antibodies (FK2) was selected because of its high specificity toward polyubiquitinated proteins [70] and was first introduced in proteomic studies of the ubiquitinome [71] ( Figure 4C). This study identified 670 proteins that were enriched under highly denaturing conditions, but lacked the detection of GG-peptides…”
Section: Ubiquitin-specific Antibodiesmentioning
confidence: 99%
“…The electrophoretic technique employed in our study, however, is less accurate for such applications. Based on our ELISA system for multiubiquitin chains, 20 development of an asymmetric ELISA for the ubiquitinated PGM-B, in which 2 antibodies to ubiquitin and the PGM-B are used for capture and detection of the antigen, respectively, is planned and it will be useful in evaluating the clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of multi-ubiquitin chains were expressed in terms of the multi-ubiquitin chain reference preparation 1 (MUCRP1). 20 …”
Section: Quantitative Analysis Of Protein and Ubiquitinmentioning
confidence: 99%
See 2 more Smart Citations